Osteopontin promotes metastasis of intrahepatic cholangiocarcinoma through recruiting MAPK1 and mediating Ser675 phosphorylation of β-Catenin - Zheng, Yan (Cell Death Dis, 2018)
The incidence and mortality of intrahepatic cholangiocarcinoma (ICC) are increasing worldwide in recent decades. Osteopontin (OPN) plays an important role in cancer metastasis, but its functional mechanism in ICC is not clear yet. In this study, we found that OPN level was elevated both in plasma and tumor tissues of ICC patients, which was closely related to a shorter overall survival (OS) and high probability of tumor relapse after curative resection. The gain- and loss-of-function studies determined that OPN could promote ICC growth and metastasis. OPN selectively interacted with β-Catenin and knockdown of β-Catenin abrogated the effects induced by OPN. OPN recruited MAPK1 and activated MEK–MAPK1 pathway to mediate the S675 phosphorylation of β-Catenin and nucleus accumulation, which induced the activation of Wnt signaling. Moreover, a significant correlation between OPN and β-Catenin was found in ICC tissues. OPN, β-Catenin, and their combination were independent prognostic indicator for ICC patients. In conclusion, OPN promotes ICC progression through recruiting MAPK1 and activating the Wnt/β-Catenin pathway and can serve as a novel prognostic marker and therapeutic target for ICC.